The relationship between maternal serum Interleukin-6 and CRP levels at first trimester of pregnancy and gestational diabetes occurrence - Fazeleh Hezareh; Lida Moghaddam-Banaem; Shadab Shahali (Mashhad University of Medical Sciences, 2021)
Introduction: Diabetes is the most common medical complication of pregnancy. Identifying the new risk factor can help to early diagnosis of the disorder. CRP and Interleukin-6 are two inflammatory markers which can anticipate some pregnancy adverse complications. This study was performed with aim to assess the relationships between maternal serum CRP and Interleukin-6 (IL-6) at first trimester of pregnancy and gestational diabetes Mellitus (GDM) occurrence. Methods: This descriptive-analytical cross-sectional study was performed in 2015-2016 on 500 pregnant women with gestational age < 14 weeks in Nilou laborator, Tehran. Serum levels of CRP, IL-6, fasting blood sugar (FBS) and lipid profile were measured. GDM screening was performed in 24-28 weeks of gestation. Data were analyzed by SPSS statistical software (version 21) and Kolmogorov-Smirnov, Chi-square, Mann-Whitney tests and Logistic regression model. P<0.05 was considered statistically significant. Results: GDM was found in 78 women (15.6%). Median CRP levels in GDM and non-GDM groups (4.8 vs. 5.22 mg/ml) (P=0.089) and median IL-6 (1.45 vs. 1.5 pg/ml) (P=0.574) was different, but the difference was not statistically significant. After adjusting the confounding variables in the logistic regression model, there were no statistically significant relations between serum level of CRP (OR=1.01, CI95%=0.96-1.07) (P=0.50) and IL-6 (OR=1.01, CI95%=0.89-1.46) (P=0.88) with GDM occurrence. Conclusion: CRP and IL-6 levels are not significantly associated with the occurrence of GDM.